Effect of Oxygen Tension on Tissue-Engineered Human Nasal Septal Chondrocytes. Issue 3 (September 2014) - Twu, Chih-Wen; Reuther, Marsha S.; Briggs, Kristen K.; Sah, Robert L.; Masuda, Koichi; Watson, Deborah
Tissue-engineered nasal septal cartilage may provide a source of autologous tissue for repair of craniofacial defects. Although advances have been made in manipulating the chondrocyte culture environment for production of neocartilage, consensus on the best oxygen tension for in vitro growth of tissue-engineered cartilage has not been reached. The objective of this study was to determine whether in vitro oxygen tension influences chondrocyte expansion and redifferentiation. Proliferation of chondrocytes from 12 patients expanded in monolayer under hypoxic (5% or 10%) or normoxic (21%) oxygen tension was compared over 14 days of culture. The highest performing oxygen level was used for further expansion of the monolayer cultures. At confluency, chondrocytes were redifferentiated by encapsulation in alginate beads and cultured for 14 days under hypoxic (5 or 10%) or normoxic (21%) oxygen tension. Biochemical and histological properties were evaluated. Chondrocyte proliferation in monolayer and redifferentiation in alginate beads were supported by all oxygen tensions tested. Chondrocytes in monolayer culture had increased proliferation at normoxic oxygen tension (p = 0.06), as well as greater accumulation of glycosaminoglycan (GAG) during chondrocyte redifferentiation (p < 0.05). Chondrocytes released from beads cultured under all three oxygen levels showed robust accumulation of GAG and type II collagen with a lower degree of type I collagen immunoreactivity. Finally, formation of chondrocyte clusters was associated with decreasing oxygen tension (p < 0.05). Expansion of human septal chondrocytes in monolayer culture was greatest at normoxic oxygen tension. Both normoxic and hypoxic culture of human septal chondrocytes embedded in alginate beads supported robust extracellular matrix deposition. However, GAG accumulation was significantly enhanced under normoxic culture conditions. Chondrocyte cluster formation was associated with hypoxic oxygen tension.